Receptor tyrosine kinases - function, families and evolution - Hunter, Tony (Henry Stewart Talks, 2007)
History of protein phosphorylation, Protein kinase bioinformatics, History of tyrosine phosphorylation and functions of tyrosine kinases, Genomic catalogues of protein kinases (kinomes), The human kinome, The evolution of kinomes, The human tyrosine kinase subfamily, Receptor and nonreceptor tyrosine kinases, Activation of receptor tyrosine kinases by ligand-induced dimerization, Signal transduction pathways downstream of receptor tyrosine kinases, Insulin and IOGF-1 receptor signaling via the mTOR pathway, mTOR-S6 kinase feedback loop leading to downregulation of the IRS1 docking protein and insulin resistance, History of Eph receptor tyrosine kinases and their ephrin ligands, Bidirectional signaling via Eph-ephrin interactions on neighboring cells, Simultaneous signaling by EphAs and ephrin As in motor neurons, Compartmentalized signaling by receptor tyrosine kinases and their ligands through localization to discrete membrane domains, Protein kinases and human disease, Human cancer genes and protein kinases, Protein kinases and phosphatases and cancer, The long road to Gleevec
Archived at 2018/05/31